O atendimento educacional especializado como uma tecnologia de governamento: a condução das condutas docentes na escola inclusiva - Hermes, Simoni Timm (2012)
Through policies of school inclusion and Special Education, Specialized Education Services (ESA) established itself as being able to complement or supplement the training of the subjects with disabilities, pervasive developmental disorders and high ability / intellectual giftedness and therefore implicated in the production of forms of teaching in inclusive school. Thus, this Master of Education s dissertation aims to understand how, through ESA, is produced and managed the teacher s conduct working in multifunctional resource rooms. It is mapping the logical operations of this Special Education s service, and it is analyzing the relationship between ESA and the inclusive education practices in neoliberalism, questioning the teacher's governing in inclusive schools. In order to achieve this aim the materiality of research includes legal documents and textbooks related to the National Network of Continuing Education of Teachers in Special Education, as well as educational projects of the ESA courses that comprise the Program of Continued Formation of Teachers in Basic Education, developed by Universidade Federal de Santa Maria(UFSM) as distance education. From Foucault studies in Education, it was used the tool governmentality in questioning the effects of the current National Policy on Special Education in the Perspective of Inclusive Education in the organization and implementation of the ESA in inclusive schools, and specifically in the continued teacher s formation. Whereas the production of a teaching subjectivity for inclusive schools as a strategy of neoliberal political rationality that pervades materiality of this research; three analytical units were built as a way to question the tactics put into operation in this process, namely: teaching in the each game and all, teaching as wanting to modify and the teaching and solidarity practice. This theoreticalmethodological enterprise it is possible to understand that political rationality, through continuous training of teachers, ensures the development of processes of individualization and totalization in Special Education as a way to manage the risk of your audience and promote the consumption and the competition. Yet, to accomplish these processes by means of scientific truth, the ESA teaches to each teacher investing in yourself, in others for as entrepreneurs themselves, participate in joint practices. Then, the same political rationality, this serves as a reference for biopolitics, which promotes the entrepreneurial self-teaching, operates in the production of joint practices in inclusive schools to ensure the success of inclusive education. The ESA as a technology of teaching government in inclusive schools.